ACADEMIC PROGRAM “DIGITAL PROJECTS LIBRARIES MANAGEMENT”: DEVELOPMENT EXPERIENCE AND IMPLEMENTATION PROSPECTS - K. V. Ivina; Yu. V. Zhegulskaya (Вестник университета)
The importance of professional training of library personnel industry, who have management and digital competences, has been substantiated. The grounds for the development of the academic program of professional training of the specialists in the field of e-libraries innovative programs and projects management have been presented. The aim and the subject matter of the Master’s academic program “Libraries E-Projects Management” in the field of training 38.04.02 “Management” have been characterized. The features of Master’s degree education program at the State University of Management have been highlighted, such as focusing on the practical aspects and transferring the studying experience into actual professional activities, the multidisciplinary approach as digital projects management personnel training strategy, cooperation with leading libraries of the country etc. The importance of attracting specialists who have not only academic degrees and titles, but also significant experience not only in library practice, but also in management activities, to teaching specialized disciplines, has been noted. The possibilities of developing an extended Master’s program focused on modern museums and archives in addition to library specialists have been indicated.